2009
DOI: 10.1021/ic802396g
|View full text |Cite
|
Sign up to set email alerts
|

Gold Complexes with the Selenolate Ligand [2-(Me2NCH2)C6H4Se]

Abstract: The reaction of [2-(Me(2)NCH(2))C(6)H(4)Se]M (M = Li, K) with the gold(phosphine) complexes [AuCl(PR(3))] gives the mononuclear gold-selenolate species [Au{SeC(6)H(4)(CH(2)NMe(2))-2}(PPh(3))] (1) or [Au{SeC(6)H(4)(CH(2)NMe(2))-2}(PPh(2)py)] (2), respectively. The treatment of the [2-(Me(2)NCH(2))C(6)H(4)Se]M with [Au(2)Cl(2)(mu-P-P)] [P-P = bis(diphenylphosphino)methane (dppm), bis(diphenylphosphino)ethane (dppe), 1,1'-bis(diphenylphosphino)ferrocene (dppf)] derivatives gives complexes with stoichiometry [Au(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…(Au-Se av = 2.441 Å) are comparable to the distances observed in the gold complexes containing selone ligands[66][67][68]. The Au-Se distances (2.4391(6) and 2.4427(6) Å) in complex 2, which are longer than those of in Au(I) complex [AuCl(SeUr)] (Ur = NHC-derived selenoureas ligands) (2.353-2.398 Å)[67] and [Au 2 {SeC 6 H 4 (CH 2 -NMe 2 )-2} 2 (l-dppf)] (2.4245(5) and 2.4250(8) Å)[68].As shown in theFig. 2, there are two forms of gold in 2 unit cell.…”
supporting
confidence: 75%
“…(Au-Se av = 2.441 Å) are comparable to the distances observed in the gold complexes containing selone ligands[66][67][68]. The Au-Se distances (2.4391(6) and 2.4427(6) Å) in complex 2, which are longer than those of in Au(I) complex [AuCl(SeUr)] (Ur = NHC-derived selenoureas ligands) (2.353-2.398 Å)[67] and [Au 2 {SeC 6 H 4 (CH 2 -NMe 2 )-2} 2 (l-dppf)] (2.4245(5) and 2.4250(8) Å)[68].As shown in theFig. 2, there are two forms of gold in 2 unit cell.…”
supporting
confidence: 75%
“…7 Recently, we have shown that trialkyl/aryl gold(I) chlorides (R 3 PAuCl, R = Me, Et or Ph) inhibit the GPx activity of the selenol 5 by forming gold(I)-selenolate complexes (6-8). 8 Gimeno and co-workers reported similar gold-selenolates (9)(10) bearing the N,N-dimethylbenzylamine moiety (figure 2). 9 It has been reported that the amino group in 5 plays an important role in the GPx activity as the Se• • • N non-covalent interactions in the key catalytic intermediates modulate the catalytic activity.…”
Section: Introductionmentioning
confidence: 93%
“…8 Gimeno and co-workers reported similar gold-selenolates (9)(10) bearing the N,N-dimethylbenzylamine moiety (figure 2). 9 It has been reported that the amino group in 5 plays an important role in the GPx activity as the Se• • • N non-covalent interactions in the key catalytic intermediates modulate the catalytic activity. 8,10 In the natural GPx enzyme, two amino acid residues, glutamine (Gln) and tryptophan (Trp), form a 'catalytic triad' with the Sec residue at the active site.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, we have reported on the synthesis, solution behaviour and molecular structures of various hypervalent organoselenium(II) compounds containing the 2-(Me 2 NCH 2 )C 6 H 4 [5,28] and 2-{Z(CH 2 CH 2 ) 2 NCH 2 }C 6 H 4 (Z ¼ O, NMe) [22] groups as well as metal organoselenolates containing the fragment [2e(R 2 NCH 2 ) C 6 H 4 ]SeeM (R ¼ Me, Et; M ¼ Au, Zn or Cd) [14,15]. As a development of these previous studies and with the aim to increase the basicity of the coordinating amine group we decided to use the 2-(N,N-diethylaminomethyl)phenyl group, 2-(Et 2 NCH 2 )C 6 H 4 , as a pendant arm ligand which can exhibit a (C,N) coordination towards the selenium centre.…”
Section: Introductionmentioning
confidence: 99%